Family Perception In Readiness Accepting Discharge Planning Determined By Nursing Advocacy Program - Judha, Mohamad (Universitas Respati Yogyakarta, 2020)
Â Planning for patients to go home raises the issue of whether the patient is ready to face health problems at home, the lack of a support system becomes a problem especially if the patient as the head of the family needs continuity of care both in the healing process and in maintaining the patient's health status both at home sick or at home. Â The purpose of this study is the role of advocacy given by nurses with readiness in receiving discharge planning by patients and families. This type of study is correlation study with cross-sectional approach in which the population in this study is the family of patients who take care of their sick family in the Internal Medicine and Surgery ward. The sampling was 97 respondents. Â Family perceptions about the role of the nurse advocacy in the positive category (73.2%). The level of family readiness in receiving discharge planning in the good category (53.6%), the results of the bivariate analysis using the Spearman Rank there is a relationship between family perceptions about nurse advocacy with readiness in receiving the discharge planning with a p-value of 0.00 <alpha 0.01, the closeness of the relationship between family perceptions about nurse advocacy with readiness to receive discharge planning in the Inpatient Ward is in the strong category with Coefficient Correlation (r) 0.641. This proves that family support is needed by patients to cure patients. Family perceptions about nurse advocacy with readiness to accept discharge planning have a strong relationship